2017
DOI: 10.15376/biores.12.3.4594-4605
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phenolic Compounds in Empty Fruit Bunches in Oyster Mushroom Cultivation and in Vermicomposting

Abstract: Analyses of total phenolic compounds were carried out for oil palm empty fruit bunches (EFBs) vermicomposting in oyster mushrooms cultivation. The oyster mushrooms (Pleurotus sajor-caju) were cultivated according to the large-scale vermicomposting trial (LSVT) methods. Both oyster mushrooms cultivation and vermicomposting of EFB with earthworms enhanced the lignin degradation of EFB. Analysis of total phenolic compounds EFB vermicomposting treated with earthworms showed a decrease in total phenolics concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This is due to several phenolic acids of CNF obtained from empty fruit bunch (EFB), such as vanillic acid, p-hydroxybenzoic acid, p-coumaric acid, ferulic acid, and vanillin. 35 Film with the present of 0.4% Eu shows highest values with (614.9290 mg GA/L sample) until 28 days of storage compared with samples without Eu significantly (p < 0.05). A decline value of phenolic content observed at 28-day storage onwards for films with Eu which suggested of degradation behavior of Eu as a result of the longer storage time.…”
Section: Antioxidant Activity Of Active Sgc-eu Filmmentioning
confidence: 84%
See 1 more Smart Citation
“…This is due to several phenolic acids of CNF obtained from empty fruit bunch (EFB), such as vanillic acid, p-hydroxybenzoic acid, p-coumaric acid, ferulic acid, and vanillin. 35 Film with the present of 0.4% Eu shows highest values with (614.9290 mg GA/L sample) until 28 days of storage compared with samples without Eu significantly (p < 0.05). A decline value of phenolic content observed at 28-day storage onwards for films with Eu which suggested of degradation behavior of Eu as a result of the longer storage time.…”
Section: Antioxidant Activity Of Active Sgc-eu Filmmentioning
confidence: 84%
“…Films without Eu such as S and SG showed no phenolic compound released into the simulant because of the absence of Eu whereas SGC exhibit phenolic compound with value range (30–40 mg GA/L). This is due to several phenolic acids of CNF obtained from empty fruit bunch (EFB), such as vanillic acid, p ‐hydroxybenzoic acid, p ‐coumaric acid, ferulic acid, and vanillin 35 . Film with the present of 0.4% Eu shows highest values with (614.9290 mg GA/L sample) until 28 days of storage compared with samples without Eu significantly ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The decomposition of cellulose and lignin follows it at high temperatures (400-1000C) (Ninduangdee et al, 2015;Sahad et al, 2014). Despite that, factors such as age and type of plantation may influence the differences in thermal degradation temperature of hemicellulose and cellulose (Yahaya et al, 2017). Stage 3 occurred when the temperatures reached 600C and were observed constant until 1000C.…”
Section: Thermal Behavior Analysismentioning
confidence: 99%
“…The death of both species was attributed to the phenolic compounds of EFB. However, Ahmad Yahaya et al (2017) observed that the amount of phenolic compounds sharply decreased in treated EFB vermicomposting using Pleurotus sajor-caju after five weeks of composting.…”
Section: Introductionmentioning
confidence: 98%